ARID1A is a useful marker of malignancy in peritoneal washings for endometrial carcinoma. Issue 4 (29th December 2014) - Nagymanyoki, Zoltan; Mutter, George L.; Hornick, Jason L.; Cibas, Edmund S.
<x xml:space="preserve">Abstract</x> BACKGROUND ARID1A (AT‐rich interactive domain 1A gene) has recently been identified as a novel tumor suppressor gene and one of the driver genes in endometrial carcinogenesis. Approximately 30% to 40% of endometrial carcinomas harbor mutations in the ARID1A gene, which results in complete loss of ARID1A protein expression. Although ARID1A aberrations are not restricted to endometrial cancer, the authors hypothesized that it might be a useful marker of malignancy in peritoneal washings for patients with endometrial cancer. METHODS The cytology archive of Brigham and Women's Hospital was searched to identify cell blocks from peritoneal washings that contained malignant or benign endometrial epithelium. From 2006 through 2013, 17 cases of endometrial carcinoma (EMCA) and 16 cases of endometriosis were identified. Surgical pathology reports and follow‐up data were used to confirm the diagnoses. Immunohistochemistry for ARID1A was performed, and slides were scored as 0 (complete loss of staining) or 1 (retained staining) by 2 independent pathologists. The discordant cases were resolved by consensus. The two‐tailed Fisher exact probability test was used to calculate statistical significance. RESULTS Complete loss of ARID1A expression was found in 8 of 17 EMCA cases (47%) and none of the 16 endometriosis cases (0%) (P = .024). The concordance among the pathologists on first review was high (96.7%). CONCLUSIONS The results of the current study demonstrated that ARID1A can be used in peritoneal washings to confirm malignancy in patients with EMCA. Complete loss of ARID1A expression by immunohistochemistry is highly specific for carcinoma, but retained expression is not informative. Cancer (Cancer Cytopathol) 2015;123:253–257. © 2014 American Cancer Society.